القیم الاجتماعیة السائدة عند تلامذة الصف الاول الابتدائي (Journal of the College of Education for Women, 2019)
The research aims at:1 - Detection of the degree of social values (truthfulness, honesty, cooperation) of theprimary first class students who compose members of the research sample in general.2 - Are there significant differences at the level (0,05%) between the average degree ofmembers of the research sample in the values (truthfulness, honesty, cooperation) amongstudents enrolled and not enrolled in kindergarten and in general.3 - Are there significant differences at the level (0,05%) between the mean scores ofindividuals in the sample values (truthfulness, honesty, cooperation) in the light of twovariables: A - Gender (male / female), b - enrolled and not enrolled in kindergarten.Having in mind that the researchers followed the descriptive approach in theanalysis of their results which they reached through the search tool, which was subject tothe procedures of the construction methodology accepted by such researches.The research shows the following results:The average degrees of members of the research sample is higher than the averagepremise.The results of this research also indicate that there are significant differencesbetween enrolled and not enrolled students in the values of truthfulness and cooperation infavour of students enrolled in kindergarten. These results don’t indicate the existence ofsignificant differences between enrolled and not enrolled in the value of honesty.With regard to the third objective, the research results indicated that there weresignificant differences between males and females in the value of truthfulness in favor offemales enrolled.With regard to the value of honesty, in the light of variables (Gender, enrollmentand not enrollment in the kindergarten) it was in favor of females.With regard to whether or not to attend kindergarten, the results show nosignificant differences between enrolled and not enrolled in kindergarten.With regard to the value of cooperation, the results of research show that there are nosignificant differences between the sexes.With regard to enrollment and non-enrollment, the research results were for thebenefit of children enrolled in kindergarten.The researchers and in the light of the results also present certainrecommendations.